Clean technologies for production of valuable fractions from sardine cooking wastewaters: an integrated process of flocculation and reverse osmosis - Pereira, Maria João (2022)
The increase in environmental consciousness and stricter regulations has motivated industries to seek sustainable technologies that allow valorising wastewaters, contributing to the profitability of overall processes. Canning industry effluents, namely sardine cooking wastewater, have a high organic matter load, containing proteins and lipids. Their untreated discharge has a negative environmental impact and an economic cost. This work aims to design an integrated process that creates value with the costly sardine cooking wastewater effluent. The research strategy followed evaluates coagulation/flocculation technologies as pre-treatment of the sardine cooking wastewater followed by reverse osmosis. Two different added-value products were obtained: a solid fraction rich in proteins, lipids (above 20%), and aromas that might be used for feed/pet/aquaculture applications and, from the processing of the resultant aqueous stream by reverse osmosis, a natural flavouring additive, which can be applied in food/feed. Additionally, the permeate from reverse osmosis presents a much lower organic load than the original raw material, which may be reused in the overall process (e.g., as water for washings) or discharged at a lower cost, with environmental benefits and economic savings.